Trade, FDI, Migration, and the Place Premium: Mexico and the United States - Davide Gandolfi; Timothy J. Halliday; Raymond Robertson (Institute for the Study of Labor (IZA), 2015)
Large wage differences between countries ("place premiums") are well documented. Theory suggests that factor price convergence should follow increased migration, capital flows, and commercial integration. All three have increased between the United States and Mexico over the last 25 years. This paper evaluates the degree of wage convergence between these countries during the period 1988 and 2011. We match survey and census data from Mexico and the United States to estimate the change in wage differentials for observationally identical workers over time. We find very little evidence of convergence. What evidence we do find is most likely due to factors unrelated to US-Mexico integration. While migration, trade, and FDI may reduce the US-Mexico wage differential, these effects are small when compared to the overall wage gap.
Keywords: F15; F16; J31; F22; 330; migration; labor-market integration; factor price equalization